ANALISIS MANAJEMEN PERSEDIAAN BAHAN BAKU PAPAN JATI PRODUKSI MEUBEL PADA PESONA MEUBEL ATAMBUA - Mindonta E Soares; Ronald P C Fanggidae; Antonio E L Nyoko (Journal of Management Small and Medium Enterprises (SMEs), 2019)
The purpose of this research is to analyze the raw materials management of Jati board in theproduction of furniture on Pesona Furniture Atambua. The aim in this research is to analyze rawmaterials supply management in the production of furniture. Data was analized using several toolsi.e Economic Order Quantity (EOQ), Safety Stock, Re-Order Point (ROP) and Divination Suppliesof Raw Materials. The research suggests precise information about the number of raw materialsprocurement using Economic Order Quantity (EOQ). Company requires to monitor the SafetyStock of raw materials and also need to determine the best time to order the raw material using themethod of Re-Order Point (ROP analysis). Keywords : EOQ, Safety Stock, ROP